GCK rs1799884 Polymorphism and Gestational Diabetes Mellitus: A System Review and Meta-Analysis - Yong Hu; Ao Wang; Ke Yi (Clinical and Experimental Obstetrics & Gynecology)
Background: The correlation among Glucokinase (GCK) rs1799884 polymorphism and the risk of gestational diabetes mellitus (GDM) remains controversial, as previous studies have reported inconsistent findings. The potential relationship among the GCK rs1799884 polymorphism and GDM risk was examined by a meta-analysis. Methods: In order to find relevant studies for our investigation, we performed an extensive search across multiple databases, such as Ovid, PubMed, China National Knowledge Infrastructure, and Web of Science. Afterward, the link among the GDM risk and GCK rs1799884 polymorphism was evaluated by employing either random-effects models or fixed-effects to compute 95% confidence intervals (CIs) and pooled odds ratios (ORs). Results: This meta-analysis comprised a total of 11 studies. The findings revealed that the GCK rs1799884 polymorphism was linked to a decreased risk of GDM across all examined models. The pooled analysis demonstrated a substantial link, with the corresponding 95% CIs and the following ORs: Allele contrast: 0.80 (0.73–0.88), recessive model 0.81 (0.76–0.88), homozygote 0.60, (0.49–0.73), heterozygote 0.84, (0.78–0.91), dominant model 0.59, (0.48–0.72). Conclusions: The GCK rs1799884 variant, according to the current meta-analysis, may act as a genetic biomarker of GDM. The investigation was registered on PROSPERO (https://www.crd.york.ac.uk/prospero/) under registration number CRD42023492185.